The Employment and Earnings Impacts of the Targeted Jobs Tax Credit - Kevin Hollenbeck; Richard J. Willke (W.E. Upjohn Institute for Employment Research, 1991)
The Targeted Jobs Tax Credit (TJTC) is intended to stimulate the employment of individuals who are members of certain groups of the labor force by providing a wage subsidy (in the form of a tax credit) to employers of recently-hired eligible workers. This intervention into the labor market has direct and indirect earnings and employment consequences for both eligible and ineligible individuals. The paper evaluates the impacts of TJTC by using a treatment and comparison group methodology. Corrections for nonrandom selection are undertaken. The primary sources of data are state quarterly wage record data from the Unemployment Insurance system and the Employment Service Automated Reporting System (ESARS). The results indicate that the availability and usage of TJTC enhances outcomes for nonwhite male youth (both eligible and ineligible), but is stigmatizing for eligible individuals from other race/sex groups, who appear to be slightly worse off because of the program than their ineligible counterparts. Obtaining a voucher increases employment and wages, but it appears as if selection effects are responsible. Importantly, the improved outcomes are not accompanied by displacement effects. Finally, being certified results in increased wages, but higher turnover and lower total employment.
Keywords: J0; J6; 330; targeted; tax; job; credit; employment; earnings; Hollenbeck; Willke